Tinjauan Model Pembelajaran Missouri Mathematics Project (MMP) untuk Meningkatkan Kemampuan Pemecahan Masalah - Imrona Hayati (STAI Sangatta Kutai Timur, 2020)
Abstract The mathematics learning objectives are to acquire the mathematical skills (mathematical literacy) needed to understand the world around it and for success in life. Problem solving is one of the most important things in learning mathematics. In fact, the problem solving ability was not as expected. Based on data from PISA, Indonesia consistently ranks in the bottom 10 in the last ten years. Therefore, it is necessary to improve learning that can deliver students to a better level. One of the efforts that can be done is to choose the right learning model. The purpose of this study was to examine the use of the Missouri Mathematics Project (MMP) learning model to improve problem solving skills. This research uses a descriptive qualitative approach. The materials and data were sourced from the review of some literature related to the Missouri Mathematics Project (MMP) learning model, MMP learning syntax (steps), mathematical problem-solving abilities, also reviews and analyzes of the application of the Missouri Mathematics Project (MMP) learning model to mathematical problem solving abilities. Based on the study, the conclusion is that the Missouri Mathematics Project (MMP) learning model is a good alternative to improve problem-solving abilities.